Biocontrol of Red Flour Beetle, Tribolium castaneum (Herbst) in Stored Wheat Using Entomopathogenic Fungi - Sahand K. Khidr; Waran N. Abdullah Agha; Qasim A. Marzani (Polytechnic)
This study was conducted to evaluate the efficacy of four entomopathogenic fungi against the red flour beetle, Tribolium castaneum (Herbst) as an alternative to chemical pesticides. The adult stage inside stored wheat was subjected to different concentrations of Beauveria bassiana (Balsamo), Metarhizium anisopliae (Metsch), Verticillium lecanii (Zimmerman), and Paecilomyces ilacinus (Thoms) in either Petri-plates at 7, 15 and 22 days or bag storage at 20, 40 and 60 days exposure times. The first experiment indicated that V. lecanii achieved maximum mortality (58.89 and 57.5%) via interaction with the highest dose of 0.748 £ 107 and maximum exposure time of 22 days respectively. The adults required the lowest concentration of V. lecanii to achieve an average LC50 (6,233,697 mg) within various exposure times. Regarding the latter experiment (liquid assay), the least survivorship (41.25) was observed by P. ilacinus followed by V. lecanii (56.25) during 60 days of exposure time. On the other hand, the powder assay revealed that the highest mortality (57.08 and 48.75) of adults inside bags was recorded respectively via the interaction terms between V. lecanii with both the highest concentration (1000 mg) and exposure times 60 days and the LC50 value of the aforementioned bioagent was (240.02) for 60 days treatment followed by B. bassiana. The study suggests that the use of biopesticides can provide significant insight in the management of pests while minimize the weight loss of stored wheat and thus, can be used as an effective alternative or integrated with chemical pesticides in pest management strategies.